Pattern of presentation of gynecological diseases in a tertiary care hospital - a hospital based study (Bangladesh Medical Journal, 2016)
This retrospective study was carried out in Shaheed Suhrawardi Medical College & Hospital (ShSMCH) from January 2013 to December 2013. Total 2160 Gynaecological patients were evaluated in 1 year period, who were admitted either from outpatient department or through emergency. The aim of this study was to observe the gynecological disease pattern, top ten gynecological diseases & organ involvement of female reproductive system. Of all patients, maximum (87%) were of reproductive age group and most of them (66%) came from urban area. Almost 78% patients admitted with uterine pathology. Among total patients 47% had pregnancy related complications, of which 86.5% patients had history of early pregnancy termination either spontaneous or induced, 7% had ectopic pregnancy and 6.5% had molar pregnancy. Of all patients, 98% had benign diseases and 2% were suffering from malignant disorder. Other gynaecological diseases were utero-vaginal prolapse, fibroid uterus, benign ovarian tumour & dysfunctional uterine bleeding.Bangladesh Med J. 2016 Jan; 45 (1): 40-43